Extraction of Henna Leaf Dye and its Dyeing Effects on Textile Fibre (Bangladesh Journal of Scientific and Industrial Research, 2007)
Henna plant leaves (Lawsonia inermis) contains dye along with other ingredients. The dye component was extracted and applied on silk fibre in order to investigate the dyeing characteristics, e.g. dyeability, fastness etc. It is found that the dye up take by silk fibre was decreased with the increase of dye concentration. Similarly the absorption of dye was increased with the decrease of dye concentration. The maximum dye absorption has been observed at 0.9 % dye with 10 % alum for the period of 65 minutes at temperature 80°C and pH 4. At this optimum condition the dye absorption was 93 %. The effects of sunlight in air on silk fibre have been studied to investigate the colourfastness. The colourfastness of dyed silk fibre of water and soap solution at different treatment temperature was satisfactory. Considering dyeability and colourfastness, dye from henna matured leaves was highly applicable on dyeing of silk fibre as well as other protein fibre.Bangladesh J. Sci. Ind. Res. 42(2), 217-222, 2007